Modeling and Simulation Research Position Control of Hydraulic Cylinder using High Speed on/off Valve is Based on the Method PWM (Pulse Width Modulation) of Control Pulse - Do, Viet Long; Hoang, Sinh Truong; Tran, Xuan Bo (Old Journal, 2019)
Application of high speed on/off valve in hydraulic cylinder position control was researched in this paper. A hydraulic circuit is proposed to position control hydraulic cylinder. The duty cycle of pulse control signal is changed according to the displacement of the hydraulic cylinder. Model of high speed on off valve and hydraulic circuit were simulated in Matlab Simulink. The Position and speed curve of hydraulic cylinder were achieved by the means of simulation. The simulation curves show the application ability of high speed on/off valve to position control of hydraulic cylinder and the ability to replace the hydraulic proportional valve.